2022
DOI: 10.3389/fnmol.2022.1036552
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing novel drugs against Keap1 in Alzheimer’s disease using machine learning grounded computational studies

Abstract: Alzheimer’s disease (AD) is the most common neurodegenerative disorder in the world, affecting an estimated 50 million individuals. The nerve cells become impaired and die due to the formation of amyloid-beta (Aβ) plaques and neurofibrillary tangles (NFTs). Dementia is one of the most common symptoms seen in people with AD. Genes, lifestyle, mitochondrial dysfunction, oxidative stress, obesity, infections, and head injuries are some of the factors that can contribute to the development and progression of AD. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…Our analysis revealed that the primary contributors to ΔGbind, which stabilizes the simulated complex, are ΔGbindCoulomb, ΔGbindvdW, and ΔGbindLipo. In contrast, ΔGbindCovalent and ΔGbindSolvGB contribute to the instability of the complex ( Mukerjee, 2022 ). These findings underscore the high binding free energy observed for the Neuropilins-PI3K complex, indicating its efficient binding capacity and ability to form a stable complex with Neuropilins.…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis revealed that the primary contributors to ΔGbind, which stabilizes the simulated complex, are ΔGbindCoulomb, ΔGbindvdW, and ΔGbindLipo. In contrast, ΔGbindCovalent and ΔGbindSolvGB contribute to the instability of the complex ( Mukerjee, 2022 ). These findings underscore the high binding free energy observed for the Neuropilins-PI3K complex, indicating its efficient binding capacity and ability to form a stable complex with Neuropilins.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it has been confirmed in numerous studies that depression as a neurodegenerative disorder resulting in atrophy of the brain regions 21 . Neurodegenerative disorders develop due to loss of neurons, resulting in a decline in cognitive functioning of the brain 22–28 . Several studies have identified the hippocampus as the key brain region linked to depression, and hippocampal plasticity occurs in patients with depression 29 .…”
Section: Overview On Depressionmentioning
confidence: 96%
“…Neurodegenerative disorders are conditions in which the central nervous system cells stop functioning or die [ 51 , 52 , 53 ]. The majority of neurodegenerative diseases are incurable and often worsen with time [ 54 , 55 ].…”
Section: Depression As a Neurodegenerative Disordermentioning
confidence: 99%